2013
DOI: 10.1111/lang.12022
|View full text |Cite
|
Sign up to set email alerts
|

Language Production and Reception: A Processability Theory Study

Abstract: Pienemann's Processability Theory (PT) predicts an order of emergence of morphosyntactic elements in second language (L2) production data. This research investigates whether the same order of emergence can be detected in L2 reception data, specifically, data from a timed audio grammaticality judgment task (GJT). The results from three related studies are reported. Overall, evidence from two groups of learners of English as an L2 who took an audio GJT does not demonstrate the order of emergence predicted by PT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
(66 reference statements)
0
16
1
Order By: Relevance
“…That is, it is not possible with these methodologies to measure the beginning moments of comprehension. Indeed, it is likely that the use of a variety of methodologies will be necessary to better understand how emergence in comprehension can be measured (see Buyl & Housen, 2015 and Spinner, 2013 for further discussion on measuring emergence with receptive tasks).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, it is not possible with these methodologies to measure the beginning moments of comprehension. Indeed, it is likely that the use of a variety of methodologies will be necessary to better understand how emergence in comprehension can be measured (see Buyl & Housen, 2015 and Spinner, 2013 for further discussion on measuring emergence with receptive tasks).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the previously described studies, Spinner (2013) included all PT stages, other than stage 1. She used an audio GJT with two groups of ESL learners of varied proficiency ( n = 114).…”
Section: Processability Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Note that almost all empirical research pertains to language production. An exception is Spinner's (2013) study, which provided support for PT with respect to language production but not with respect to language reception. Input Processing theory (VanPatten, 2012) and MOGUL (Sharwood Smith & Truscott, 2014) include language reception but do not propose stages of L2 learning.…”
Section: Issue 2: Reception and Productionmentioning
confidence: 99%
“…At the same time, however, it surprises me that no falsifications of its claims seem to have been obtained and published yet, given the considerable amount of research conducted under the PT framework. (Some concerns with PT were expressed in Bohnacker [2004], Dyson [2009], Glahn et al [2001], and Spinner [2013].) Is it true then that, as of today, nobody has found that a morphosyntactic phenomenon requiring information exchange between constituents emerged before a structure requiring information exchange within a constituent?…”
Section: Prediction Falsification and The Scope Of Theoriesmentioning
confidence: 99%